Sperm nuclear basic proteins of marine invertebrates - Török, Anna; Gornik, Sebastian G. (Marine organisms as model systems in biology and medicine, 2018)
In this chapter, a short evolutionary history and comparative analysis of sperm nuclear basic proteins (SNBPs) in marine invertebrates are presented based on some of the most recent publications in the field and building upon previously published reviews on the topic. Putative functions of SNBPs in sperm chromatin beyond DNA packaging will also be discussed with a primary focus on outstanding research questions.In somatic cells of all metazoans, DNA is packaged into tightly folded and dynamically accessible chromatin by canonical histones H2A, H2B, H3 and H4. Sperm chromatin of many animals, on the other hand, is organised by small yet structurally highly heterogeneous proteins called SNBPs, which can package sperm DNA on their own or in combination with each other. In extreme cases, sperm chromatin is condensed into a volume 6-10 times smaller than that of a somatic nucleus. SNBPs are classified into three major groups: H1 histone-type proteins (H-type SNBPs), protamines (P-type SNBPs) and protamine-like proteins (PL-type SNBPs). P-type SNBPs are mostly found in vertebrates, while PL-type SNBPs are ubiquitous in many invertebrate phyla. PL-type and P-type SNBPs evolved from histone H-type SNBP precursors through vertical evolution. Porifera, Ctenophora and Crustacea, Echinoidea (phylum Echinodermata) and Hydrozoa (phylum Hydrozoa) lack SNBPs. Echinoidea and Hydrozoa, however, evolved novel nucleosomal histone variants with specific roles during spermatogenesis. Seemingly, chromatin condensation plays a critical role in the silencing and tight packing of the genome within the sperm nucleus of most animals. However, the question of what necessitates the compaction of some sperm DNA beyond classical nucleosomal packaging while other sperm function using ‘normal’ histones remains unanswered to date.